Effectiveness of Oral Magnesium on Clinical Outcomes of Meningitis Patients at Dr. Mohammad Hoesin General Hospital Palembang - Vernandi, Andra; Andika Okparasta (Jurnal RSMH Palembang, 2023)
Meningitis is an infection of the meninges that has high mortality and morbidity. Magnesium is an enzyme co-factor that plays a role in cellular physiology. Administration of magnesium has a neuroprotective effect that potential to improve the clinical outcome of meningitis patients. An experimental knowing the effectiveness of oral magnesium on clinical outcomes in meningitis patients at RSUP Dr. Mohammad Hoesin General Hospital Palembang and this is a randomized control trial (RCT) using the add-on and double-blind method in meningitis patients by measuring the Bartel Index (BI) and Modified Rankin Scale (MRS) scales at RSMH for the period 1 September 2022 – 30 November 2022. There were 30 meningitis patients, 13 patients (43.3%) were dominated by tuberculous meningitis, and another types of meningitis were bacterial meningitis, cryptococcal/fungal meningitis and viral meningitis for 11 patients (36.7%), 4 patients (13, 3%) and 2 patients (6.7%) with female sex 16 patients (53.3%) and male 14 patients (46.7%). The difference of value between BI and MRS, the magnesium group is better than the placebo group with a comparison value of 49,333 and 45.33 for the Bartel Index and comparison value of 2,867 and 2,533 for the modified rankin scale. However, this difference was not statistically different with p value > 0.05. The conclusion is there was an increase in BI and MRS values in both the placebo and magnesium groups with the increase in BI and MRS values being higher in the magnesium group.